Facet junction of BiOBr nanosheets boosting spatial charge separation for CO2 photoreduction. (February 2022) - Meng, Jiazhi; Duan, Youyu; Jing, Shaojie; Ma, Jiangping; Wang, Kaiwen; Zhou, Kai; Ban, Chaogang; Wang, Yang; Hu, Bihao; Yu, Danmei; Gan, Liyong; Zhou, Xiaoyuan
Abstract: Understanding on the photogenerated charge separation from a microscopic level remains a challenge and is highly desirable as it provides a cornerstone for designing high-performance photocatalysts. Herein, facet engineering is chosen as a tool to reveal the relationship between the charge separation/transfer and crystal structure. A series of BiOBr nanosheets with dominantly exposed facet of (001) or (010) as well as different lateral facet exposure ratios are constructed via adjusting pH value during the hydrothermal process. It is found that exposure of anisotropic crystal facets allows the separative transfer of photogenerated electrons and holes onto the lateral facets and dominantly exposed facets, respectively, which is attributed to the junction formed between distinct facets (i.e., facet junction). In the case of BiOBr-5 with (010)/(102) facet junction, the electron transfer rate ( k ET ) and efficiency ( η ET ) are 3.658 × 10 6 s −1 and 54.09%, which are superior than the counterpart of BiOBr-1 with (001)/(110) facet junction. The fast electron transfer rate and high transfer efficiency of BiOBr-5 result in the high CO evolution rate from CO2 photoreduction under artificial sunlight. Our work may bring some new insights into the mechanism of facet junction and rational design of photocatalysts with high performance for solar energy storage in future. Graphical Abstract: The (010)/(102) facet junction on the BiOBr nanosheet was used for efficient charge separation and transport. its fast electron transfer rate and high transfer efficiency result in the high CO evolution rate from CO2 photoreduction under artificial sunlight. Our work may bring some new insights into the mechanism understanding of facet junction and rational design of photocatalysts with high performance for solar energy storage in future. ga1 Highlights: BiOBr nanosheets with different facet junctions were synthesized for photocatalytic CO2 reduction. The (010)/(102) facet junction presents more favorable charge separation and transfer performance than (001)/(110). Such charge separation in (010) / (102) facet junction facilitates the efficient conversion of CO2 into CO.